Computational Studies of the Luciferase Light-Emitting Product: Oxyluciferin - da silva, lp (2011)
Firefly luciferase is the most studied bioluminescence system, and its catalyzed reactions have been relatively well characterized. However, the color tuning mechanism that leads to firefly multicolor bioluminescence is still unknown, nor is consensual which is the yellow-green and red emitters. Computational studies have been essential in the study of oxyluciferin (OxyLH(2)) chemi- and bioluminescence and are responsible for most of our knowledge of this natural phenomenon. The objective of this manuscript is the analysis of the benefits and the conclusions derived from the theoretical studies of the light emitter, OxyLH(2), and its applications on bioluminescence research.